Respon Tekanan Transient Pada Reservoir Gas Multilayer Dengan Hydraulic Fracturing - M. Mahlil Nasution; Nugroho Marsiyanto; Citra Wahyuningrum (JURNAL BHARA PETRO ENERGI, 2023)
Abstract Transient pressure analysis is designed to provide a quantitative analysis of reservoir properties. The data from the test results are collected to support information on a reservoir which is then used to become a predictive model and update the geological model. Based on the type, Pressure Transient is divided into pressure Build up and Pressure Drawdown. In testing, Pressure Transient analysis can describe the characteristics of the reservoir properties or the formation's ability to produce fluid. This test has advantages compared to other techniques in determining reservoir characteristics, because the transient pressure test covers a larger area so that it allows estimation of porosity, reservoir permeability, average pressure, skin, fracture length, reservoir heterogeneity, drainage area, shape, and even distance. can reach up to the boundary or flow discontinuities. Keywords: Reservoir, Pressure Build Up, Pressure DrawDown, Hydraulic Fracturing, Transient Pressure Abstrak Analisa tekanan transien dirancang untuk memberikan analisis kuantitatif dari sifat- sifat reservoir. Data-data hasil pengujian tersebut dikumpulkan Untuk dapat digunakan menjadi data penunjang informasi suatu reservoir yang kemudian akan digunakan sebagai model prediktif serta memperbarui model geologi. Jika di Klasifikan menurut jenisnya maka Pressure Transient dapat dibagi menjadi dua yaitu  pressure Build up dan Pressure Drawdown. Dalam suatu pengujian analisa dari  Pressure Trasient akan dapat menggambarkan karakter atau sifat dari suatu reservoir atau kemampuan dari  formasi untuk bisa menghasilkan suatu fluida. Pengujian ini memiliki kelebihan apabila dibandingkan dengan teknik atau metode lain dalam menentukan karakteristik atau sifat dari reservoir, hal ini  dikarenakan pengujian tekanan transient dapat mencakup daerah yang jauh lebih besar sehingga jal ini memungkinkan estimasi atau perkiraan dari harga  porositas, tekanan rata-rata, permeabilitas reservoir, panjang fraktur, skin, heterogenitas reservoir, jarak, bentuk, bahkan luas drainase nya dapat di perkirakan  hingga mencapai  bidang batasnya (boundary) atau yang lebih dikenal dengan istilah flow discontinuities. Kata kunci: Reservoir, Pressure Build Up, Pressure Drawdown, Hydraulic Fracturing, Tekanan Transient. Reference: Yew, C. H. (1978). Mechanics of Hydraulic Fracturing. Texas : Gulf Publishing Company. Williams, B. B., Gidley, J. L., Schechter, R. S. (1979). Acidizing Fundamentals. New York : AIME. Anonim. (2003). Perencanaan Hydraulic Fracturing. Jakarta : Pertamina Handbook Perencanaan Stimulasi (Pdf). Schechter, R. S. (1992). Oil Well Stimulation. Englewood Cliffs New Jersey : Prentice Hall. Petroleum Engineer Field Pendopo. (2012). Data Produksi, Data Reservoir, Data Komplesi Sumur MHL-11. Laporan Kerja Fungsi Petroleum Engineer. Prabumulih: PT Pertamina Hulu Rokan. Economides, M. J., Martin, T. (2007). Modern Fracturing, Enhancing Natural Gas Production. Houston : ET Publishing. James, S. S. (2012). Post Job Report SPA -028 Spectra Frac 4000 with 20/40 carbolite. Pendopo : BJ Service. Economides, M. J., Hill, A. D., Ehlig, C. (1994). Petroleum Production System. New Jersey : Prentice Hall. Economides, M. J., Nolte, K. G. (1989). Reservoir Stimulation. New Jersey : Prentice Hall. 10. Golan, M., Whitson, C. H. (1991). Well Performance. Norway : Prentice Hall Rasyid, A., & Lestari, T. S. (2018). Penentuan Produktivitas Zona Minyak Dengan Menggunakan Modular Formation Dynamic Technology. Jurnal Kajian Ilmiah, 18(1).